LAYERED DEFENSE IN COMMUNICATION SYSTEMS: JOINT USE OF VPN PROTOCOLS AND LINEAR BLOCK CODES - Vladyslav Sharov; Olena Nikulina (Вісник Національного технічного університету "ХПÌ": Системний аналіз, управління та інформаційні технології, 2025)
With the rapid increase in the volume of transmitted information and the proliferation of distributed network infrastructures, the requirements for the security and reliability of communication channels are steadily intensifying. Traditional protection methods, such as virtual private networks (VPNs), are primarily aimed at ensuring confidentiality and authenticity through cryptographic algorithms, while typically lacking resilience to transmission-level errors arising from noise, interference, or hardware failures. In contrast, error correction codes—such as Hamming codes—are well-established tools for detecting and correcting random errors in physical channels, but they do not address intentional threats like interception, modification, or traffic analysis. This paper presents a hybrid cascading model for secure and reliable data transmission that integrates cryptographic encapsulation via VPN technologies with structural redundancy provided by error correction coding. A specific focus is placed on the use of Hamming codes extended by an additional parity bit applied at the post-encryption stage, enabling the protection of VPN packet integrity even under noisy channel conditions. The architecture of the proposed model is examined in detail, including its modular components, processing flow, and the various possible configurations of encoding and encryption blocks. Particular attention is given to analysing the threat surfaces present at each phase of transmission—prior to tunneling, during transport, and at the decryption stage—and assessing the system’s robustness through probabilistic reliability metrics and redundancy coefficients. Simulation-based modelling supports the theoretical framework and confirms that the combined use of encryption and redundancy coding significantly enhances overall communication resilience. The results underscore the importance of a comprehensive approach to secure data transmission that jointly addresses logical security threats and physical-level vulnerabilities.